PENGARUH KEPEMILIKAN MANAJERIAL DAN KOMITE AUDIT TERHADAP OPINI AUDIT GOING CONCERN - Indra Saputra; Muhammad Halim (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This purpose of this study was to found whether effect managerial ownership and audit committee on going concern audit opinion Manufacturing Companies on the Indonesia Stock Exchange (IDX) for the 2017–2019 Period. The sample drawn by purposive sampling and fulfill sample selection criteria. Method of data analysis using logistik regression. The results of the study show that the managerial ownership variable has an effect on the Going Concern audit opinion, while the audit committee has no effect on the going concern audit opinion. The results of the research simultaneously that managerial ownership and the audit committee have an effect on going concern audit opinions. The results of the R square test of Managerial Ownership and the audit committee affect the Going Concern Audit Opinion by 47.8% and the remaining 52.2% is influenced by other variables or factors.